2007
DOI: 10.1159/000099019
|View full text |Cite
|
Sign up to set email alerts
|

Residual Hearing Thresholds in Cochlear Implantation and Reimplantation

Abstract: Implant and reimplantation surgery should be carried out with preservation of residual hearing. The aim of this study is to evaluate the effects of such a surgery on hearing threshold. We report the results on 40 patients, 20 males and 20 females, aged between 5 and 70 (mean 29) years, 16 pre-verbal and 24 post-verbal, with measurable pre-operative auditory thresholds. We used the following implants: Advanced Bionics, Med-El, Cochlear, and MXM Digisonic. Four of the patients underwent cochlear reimplantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The transmission of acoustic stimuli by bone conduction to elicit VEMPs should also be possible because the saccule is neuroanatomically closer to the oval window than to the round window where the cochlear implant electrode was inserted. This is supported by reports of airand bone-conducted residual hearing after cochlear implantation [Gstoettner et al, 2006;Di Nardo et al, 2007]. Unfortunately, all patients investigated in the present study had no significant residual hearing before surgery so that this aspect could not be further investigated.…”
Section: Discussionsupporting
confidence: 64%
“…The transmission of acoustic stimuli by bone conduction to elicit VEMPs should also be possible because the saccule is neuroanatomically closer to the oval window than to the round window where the cochlear implant electrode was inserted. This is supported by reports of airand bone-conducted residual hearing after cochlear implantation [Gstoettner et al, 2006;Di Nardo et al, 2007]. Unfortunately, all patients investigated in the present study had no significant residual hearing before surgery so that this aspect could not be further investigated.…”
Section: Discussionsupporting
confidence: 64%
“…In 2001, the same group had reported that in a series of 33 reimplantations over 16 years they had measured postoperative performance at equal or better scores than before failure [2] . In a recent publication by Di Nardo et al [12] , the authors investigated residual hearing thresholds that had been retained after initial implantation. In 3 out of 4 individuals residual hearing was even preserved after the reimplantation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These surgical challenges were investigated in numerous studies [34,[36][37][38] showing a strong fluctuation in the success rate. The range of reported complete preservation of residual hearing varies from 26% [34] to 39% [38].…”
Section: Discussionmentioning
confidence: 99%